1986
DOI: 10.1149/1.2108377
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Absorption of Chloride Ions on Passive Iron Systems

Abstract: The adsorption and absorption of chloride on iron in borate buffer solution have been studied using a radiotracer technique. The two processes are clearly distinguishable by their different time constants, ∼ 1 min for adsorption and ∼ 1h for absorption. The adsorpton of chloride on bare iron and passive layer surfaces follows the Tempkin type of isotherm. The free energy of adsorption of chloride on passive layer is significantly higher than that on bare iron. Partial charge transfer between adsorbed chloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…It can be concluded that the model is conceptually correct but needs scaling: it attempts to embrace processes occurring across a range of scales from atomistic to macroscopic and it is difficult to see how these mechanisms relate to each other and how they impact on the observed property changes. Jovancicevic et al (1986) conclude that desorption and absorption of chloride on iron are two distinct processes. Adsorption, being potential and concentration dependent, is stronger in the passive layer than on bare iron, which is explained by a charge transfer between chloride (Cl À ) and iron (Fe 2+ and/or Fe 3+ ).…”
Section: Advances In Cement Researchmentioning
confidence: 85%
See 4 more Smart Citations
“…It can be concluded that the model is conceptually correct but needs scaling: it attempts to embrace processes occurring across a range of scales from atomistic to macroscopic and it is difficult to see how these mechanisms relate to each other and how they impact on the observed property changes. Jovancicevic et al (1986) conclude that desorption and absorption of chloride on iron are two distinct processes. Adsorption, being potential and concentration dependent, is stronger in the passive layer than on bare iron, which is explained by a charge transfer between chloride (Cl À ) and iron (Fe 2+ and/or Fe 3+ ).…”
Section: Advances In Cement Researchmentioning
confidence: 85%
“…Jovancicevic et al (1986) classified the existing models for describing the action of chloride on passive layer breakdown into three stages in terms of the mechanisms involved…”
Section: Interaction With Chloridementioning
confidence: 99%
See 3 more Smart Citations